Effect of Ground Seeds of Picralima nitida Incorporated Diets on Serum Lipid Profile of Albino Rats - Nwaogu, L. A; Emejulu, A. A.; Udebuani, A. C. (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The effect of ground seeds of Picralima nitida incorporated diets on serum lipid profile of albino rats was studied. Twenty five albino rats randomly distributed into five groups of five rats were fed with 5%, 10%, 20% and 30% w/w concentrations of ground seeds of Picralima nitida incorporated diets for 28 days. The concentrations of serum triacylglycerols (TGs), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), positive atherogenic index (HDL-C/TC) and negative atherogenic index (LDL-C/HDL-C) of the serum of albino rats fed with these percentage concentrations of ground seeds of Picralima nitida incorporated diets were determined using standard methods. Albino rats fed with guinea feed without ground seeds of Picralima nitida served as the control. Results obtained show that there was a significant (p<0.05) decrease in the concentrations of triacylglyceroles, low-density lipoprotein as the concentrations of ground seeds of Picralima nitida increased in contrast to a gradual significant (p>0.05) increase in the concentrations of serum cholesterol at 10% and a significant (p<0.05) reduction in the concentrations of high-density lipoprotein cholesterol (LDH-C) at high concentration of 30% of the ground seeds of P. nitida incorporated diets, when compared to those of the control. Positive atherogenic index (HDL-C/TC) showed a significant (p<0.05) reduction at 30% while negative atherogenic index (LDL-C/HDL-C) was significantly (p<0.05) lower from 10% when compared to those of the control. These observed changes, as a result of administration of ground seeds of P. nitida incorporated diets indicate that these plant seeds have hypolipidaemic potential on the serum of experimental albino rats.